2010
DOI: 10.1245/s10434-009-0901-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Methylation of Specific Genes is Associated with the Phenotype and Progression of Colorectal Adenocarcinomas

Abstract: The study suggests that specific CIMP markers, such as p16 ( INK4a ) and MINT31, should be further verified as potential epigenetic targets for the design of efficient chemotherapy regimens. We also identified a subset of colorectal cancer, possibly comprising APC methylation-KRAS mutation-p16 ( INK4a ) methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 38 publications
3
45
3
3
Order By: Relevance
“…We observed DAPK methylation in 11.1% of the patients. This value is somewhat lower than previous reports for HNC (Nayak et al, 2007;Steinmann et al, 2009) but in concordance with the frequencies observed in colon (Kim et al, 2010) and breast cancer (Buyru et al, 2009), multiple myeloma (Galm et al, 2004;Braggio et al, 2010), and acute myeloid leukemia (Galm et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…We observed DAPK methylation in 11.1% of the patients. This value is somewhat lower than previous reports for HNC (Nayak et al, 2007;Steinmann et al, 2009) but in concordance with the frequencies observed in colon (Kim et al, 2010) and breast cancer (Buyru et al, 2009), multiple myeloma (Galm et al, 2004;Braggio et al, 2010), and acute myeloid leukemia (Galm et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…The following electronic databases were searched for relevant articles without any language restrictions: Web of Science (1945∼2014), the Cochrane Library Database (Issue 12, [27] 2011 Egypt 36 MSP Chen et al [28] 2 0 0 9 C h i n a 1 1 7 M S P Kim et al [29] 2010 Korea 570 Pyrosequencing Kohonen-Cosish et al [22] 2 0 0 5 A u s t r a l i a 1 8 3 M S P Krtolica et al [30] 2007 Belgrade 46 31.4 mo MSP Lee et al [31] 2 0 1 1 K o r e a 3 3 6 M S P Mokarram et al [32] 2 0 1 3 I r a n 9 2 M S P Nagasaka et al [6] 2 0 0 8 J a p a n 5 9 3 M S P Nagasaka et al [33] 2003 Japan 90 MSP Nilsson et al [7] 2013 Sweden 163 60 mo Pyrosequencing Shima et al [24] 2011 USA 124 156 mo q-MSP Sinha et al [34] 2013 India 855 2 mo MSP Zhang et al [25] 2011 China 24 23 mo MSP mo month, q-MSP quantitative methylation-specific PCR We searched articles using the following terms: MGMT promoter methylation and colorectal cancer or adenoma or normal tissue. We included studies that met the following criteria: (1) the association between MGMT methylation and CRC, and/or adenoma and (2) the association of MGMT methylation and prognosis in CRC patients.…”
Section: Articles Search Strategy and Selection Criteriamentioning
confidence: 99%
“…[3][4][5] Additionally, APC is a CRC progression marker, 6 and its expression maybe downregulated in precancerous adenomatous tissue via promoter hypermethylation. 7 Likewise, 3OST2 is highly methylated (82%) in CRC, including sporadic and Lynch Syndrome CRC.…”
Section: Introductionmentioning
confidence: 99%